Republic of Poland : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Poland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The external sector has an increasing drag on the economy. The current account deficit remains fully financed by FDI, and the underlying balance is consistent with external-debt stabilizing levels. The stock market retrenchment has been severe, but it followed substantial gains since 2006. Stress tests show that resilience of the banking system is well capitalized and highly profitable. Executive Directors stressed that the key to boosting long-term growth will be to increase low labor market participation. The financial supervision authority should give priority to formalizing understandings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet